Impact of Renal Function on Outcomes With Edoxaban in the ENGAGE AF-TIMI 48 Trial. Issue 1 (5th July 2016) - Bohula, Erin A.; Giugliano, Robert P.; Ruff, Christian T.; Kuder, Julia F.; Murphy, Sabina A.; Antman, Elliott M.; Braunwald, Eugene
Abstract : BACKGROUND: Edoxaban, an oral factor Xa inhibitor with 50% renal clearance, was noninferior to well-managed warfarin for stroke or systemic embolism (S/SE) prevention and reduced bleeding in patients with atrial fibrillation. We evaluated the efficacy and safety of edoxaban versus warfarin across the range of baseline creatinine clearance (CrCl) in the ENGAGE AF-TIMI 48 trial (Effective Anticoagulation With Factor Xa Next Generation in Atrial Fibrillation–Thrombolysis in Myocardial Infarction Study 48) with a focus on the higher-dose edoxaban regimen (HDER) and the upper range of CrCl. METHODS: A total of 14 071 patients with atrial fibrillation at moderate to high risk for stroke were randomized to warfarin or HDER (60 mg daily or a 50% dose reduction to 30 mg daily for CrCl 30–50 mL/min, body weight of ⩽60 kg, or use of a potent phosphorylated glycoprotein inhibitor). CrCl <30 mL/min was exclusionary. End points of S/SE, International Society on Thrombosis and Haemostasis major bleeding, and the net clinical outcome of S/SE/major bleeding or death were evaluated by intention-to-treat analysis using the prespecified CrCl cut point of 50 mL/min and additional exploratory cut points with the Cockcroft-Gault formula. A sensitivity analysis was performed with the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) formula for estimating renal function. RESULTS: The relative risk of S/SE with HDER versus warfarin in patients with CrCl >50 mL/min (hazard ratio [HR], 0.87; 95% confidence interval [CI], 0.72–1.04) was similar to that in patients with CrCl ⩽50 mL/min (HR, 0.87; 95% CI, 0.65–1.18; P for interaction=0.94). Several exploratory analyses suggested lower relative efficacy for the prevention of S/SE with HDER compared with warfarin at higher levels of CrCl (CrCl ⩽50 mL/min: HR, 0.87; 95% CI, 0.65–1.18; CrCl >50–95 mL/min: HR, 0.78; 95% CI, 0.64–0.96; CrCl >95 mL/min: HR, 1.36; 95% CI, 0.88–2.10; P for interaction=0.08). Bleeding rates were lower at all levels of CrCl with HDER ( P for interaction=0.11). Because of the preserved effect on bleeding, the net clinical outcome was more favorable with HDER across the range of CrCl ( P for interaction=0.73). Similar findings were observed in the sensitivity analysis using the CKD-EPI formula. CONCLUSIONS: Although there was an apparent decrease in relative efficacy to prevent arterial thromboembolism in the upper range of CrCl, the safety and net clinical benefit of HDER compared with warfarin are consistent across the range of renal function. CLINICAL TRIAL REGISTRATION: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00781391. Abstract : Supplemental Digital Content is available in the text.